Nutrient Fortification of Human Donor Milk Affects Intestinal Function and Protein Metabolism in Preterm Pigs. Issue 3 (12th March 2018) - Sun, Jing; Li, Yanqi; Nguyen, Duc Ninh; Mortensen, Martin S; van den Akker, Chris HP; Skeath, Tom; Pors, Susanne E; Pankratova, Stanislava; Rudloff, Silvia; Sørensen, Søren J; Burrin, Douglas G; Thymann, Thomas; et al.
Abstract: Background: Nutrient fortification of human milk is often required to secure adequate growth and organ development for very preterm infants. There is concern that formula-based fortifiers (FFs) induce intestinal dysfunction, feeding intolerance, and necrotizing enterocolitis (NEC). Bovine colostrum (BC) may be an alternative nutrient fortifier, considering its high content of protein and milk bioactive factors. Objective: We investigated whether BC was superior to an FF product based on processed bovine milk and vegetable oil to fortify donor human milk (DHM) for preterm pigs, used as a model for infants. Methods: Sixty preterm pigs from 4 sows (Danish Landrace × Large White × Duroc, birth weight 944 ± 29 g) received decreasing volumes of parenteral nutrition (96–72 mL ⋅ kg −1  ⋅ d −1 ) and increasing volumes of enteral nutrition (24–132 mL ⋅ kg −1  ⋅ d −1 ) for 8 d. Pigs were fed donor porcine milk (DPM) and DHM with or without FF or BC fortification (+4.6 g protein ⋅ kg −1  ⋅ d −1 ). Results: DPM-fed pigs showed higher growth (10-fold), protein synthesis (+15–30%), villus heights, lactase and peptidase activities (+30%), and reduced intestinal cytokines (–50%) relative to DHM pigs (all P < 0.05). Fortification increased protein synthesis (+20–30%), but with higher weight gain and lower urea and cortisol concentrations for DHM+BC compared with DHM+FF pigs (2- to 3-fold differences, all P ≤ 0.06). DHM+FF pigs showed more diarrhea and reduced lactase and peptidase activities, hexose uptake, and villus heights relative to DHM+BC or DHM pigs (30–90% differences, P < 0.05). Fortification did not affect NEC incidence but DHM+BC pigs had lower colonic interleukin (IL)-6 and IL-8 concentrations relative to the remaining pigs (–30%, P = 0.06). DHM+FF pigs had higher stomach bacterial load than did DHM, and higher bacterial density along intestinal villi than did DHM and DHM+BC pigs (2- to 3-fold, P < 0.05). Conclusions: The FF product investigated in this study reduced growth, intestinal function, and protein utilization in DHM-fed preterm pigs, relative to BC as fortifier. The relevance of BC as an alternative nutrient fortifier for preterm infants should be tested.